Recent Developments in Heterogeneous Catalysis of N-Methylation Reaction with CO₂ - Luo, Peikai; Gong, Qihang; Su, Xinluona; Cheng, Haiyang (Sustainability & Circularity NOW, 2025)
A promising strategy for reducing CO₂ emissions is to catalyze the conversion of CO₂ into high-value products, such as N-methylamines, which serve as key intermediates in various industries including pharmaceuticals, agrochemicals, and fine chemicals. This review summarizes recent advancements in the application of heterogeneous catalysts for the N-methylation of amines via CO₂ hydrogenation. Various types of catalysts are discussed, including noble metal-based catalysts (e.g., Pd, Ag, Au, Pt, and Ru), non-noble metal catalysts (e.g., Cu and Zn), and non-metallic catalysts (e.g., nitrogen-doped carbon materials). The review analyzes catalyst performance, reaction conditions, and reaction mechanisms, with a focus on the relationship between catalytic activity, product yield, reaction mechanisms and support, metal, modifier, and so on in the catalytic process.
Keywords: CO2; N-methylation; Hydrogenation; Heterogeneous catalysis